2003
DOI: 10.4049/jimmunol.170.10.5064
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Independent CTL Suppression during Tumor Progression: Association with Arginase-Producing (M2) Myeloid Cells

Abstract: Most of the mice bearing a s.c. BW-Sp3 lymphoma tumor mount a CD8+ T cell-mediated response resulting in tumor regression. Nonetheless, tumor progression occurs in some of the recipients and is associated with CTL inactivity. We demonstrated that T cell-activating APC were induced in regressors whereas T cell suppressive myeloid cells predominated in the spleen of progressors. Indeed, in vitro depletion of either the adherent or the CD11b+ populations restored T cell cytotoxicity and proliferation in these mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 70 publications
1
93
1
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10] However, the term MDSC covers a heterogeneous population of cells, which in mice are characterized by CD11b and Gr-1 coexpression. For a thorough understanding of the biology and activities of these cells, it is crucial to tackle their heterogeneity and to evaluate the origin and function of different MDSC subpopulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9][10] However, the term MDSC covers a heterogeneous population of cells, which in mice are characterized by CD11b and Gr-1 coexpression. For a thorough understanding of the biology and activities of these cells, it is crucial to tackle their heterogeneity and to evaluate the origin and function of different MDSC subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…1 In this regard, tumors are found to affect myelopoiesis and induce the expansion of myeloid cells with immunosuppressive activity, in both animal models and human patients. [2][3][4][5][6][7][8][9][10] These cells are referred to as myeloid-derived suppressor cells (MDSCs), which are in mice typically identified by the coexpression of the CD11b and Gr-1 surface markers. 11 Tumor-induced CD11b ϩ Gr-1 ϩ cells accumulate in the bone marrow, spleen, and blood, and are considered to be a heterogeneous population consisting of different myeloid cell types in various maturation states.…”
Section: Introductionmentioning
confidence: 99%
“…35 As opposed to classically activated (M1) macrophages, alternatively activated (M2) macrophages can inhibit T-cell function, 36 in part through expression of arginase I. 37,38 To determine the differentiation of the tumour macrophages, we examined the expression of characteristic M1 and M2 markers as described by Mantovani et al 39 Interestingly, the tumour macrophages showed a mixed M1 and M2 pattern of gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that our model system lacks CD4 ϩ CD25 ϩ regulatory T cells as well as B cells that could be inhibitory for antitumor CD8 ϩ T cells (36). However, myeloid suppressor cells producing arginase (34,35) or indoleamine-2,3-dioxygenase (33,54,55), or induced expression of inhibitory ligands like PD-L1/B7-H1 (44) or B7.x/B7H4 (56) on the tumor cells or by infiltrating host cells could theoretically contribute to T cell dysfunction in vivo. It is worth noting that the hyporesponsiveness occurs when the tumors are quite large, which supports the notion that some change occurs in the tumor over time that may contribute to T cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy also has been shown to up-regulate expression of adhesion molecules such as ICAM-1 on vascular endothelial cells (30). In addition, the depleting properties of these interventions might favor relative loss of suppressor populations, such as CD4 ϩ CD25 ϩ regulatory T cells (31), myeloid suppressor cells (32)(33)(34)(35), or B cells (36), and thus may do more than just provide a lymphopenic state. The T cell repertoire also may be altered in response to these conditioning regimens, favoring representation of recent thymic emigrees that may display a different array of Ag specificities.…”
mentioning
confidence: 99%